dalam pementasan sebagai kajian esensi di jurusan teater STKW sSurabaya - LESTARI, LILIS (Universitas Negeri Surabaya, 2024)
Supali's acting style in the play Supali gendeng Wedokan (SGW) is an original research by the author, which is an academic work to find out Supali's acting style as a creative East Javanese actor who reacts in folk theater performances such as ludruk. Ludruk has become a traditional theater that has meaning as a good learning medium in society, especially East Java. As a study, it is necessary to examine the rich acting of ludruk actors who maintain the atmosphere of ludruk art until it is owned by the interested community. Supali is not even distant from the community, the figure of Supali has become an icon in every performance he plays so that every presence in the performance is always attended by his fans, namely the community, especially East Java. The purpose of this research is to find out the extent of the development and progress of Supali's acting style as an Indonesian traditional theater actor, especially when playing roles in the SGW play. Based on the overall description that has been done in the form of analysis, the answer to the formulation of this research problem, Supali's acting style in the performance of